PERANAN KEPEMIMPINAN CAMAT DI KECAMATAN BATU AMPAR TERHADAP PEMELIHARAAN BARANG MILIK DAERAH - Arsuni Arsuni (ADMINISTRASI PUBLIK, 2019)
This study aims to find out how the Role of Camat Leadership in Batu Ampar District Against the Maintenance of Regional Property.The timing of the research is carried out in December 2018 until May 2019 for 5 (five) months. The research method in this study is descriptive with a descriptive analysis of the percentage, the data obtained through direct observation to the field and distributing questionnaires to the speakers with a sample size of 31 (thirty one) respondents.Based on the analysis of the data obtained using questionnaires obtained a percentage value of 70% with very good value, the average score is 4.29. According to Umar (2002), the value of 4.29 falls into the very good category.